2010
DOI: 10.1136/ip.2010.029215.129
|View full text |Cite
|
Sign up to set email alerts
|

Disaster management in University Libraries: perception, problems and strategies

Abstract: The paper investigated disaster management in University Libraries in South Eastern Nigeria; perceptions, problems and strategies. The design of the study was a descriptive survey. The population of the study consisted of librarians from university libraries in Southern Nigeria. Eighty-six librarians were sampled from the total of 265 librarians. Three research questions guided the study. Data for the study were collected using questionnaire which was validated through expert opinion. Data generated for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…On another hand, the result of this study corroborated that of Echezona, Ugwu and Ozioko [16] who noted that it has been an age long thinking of librarians that the chances of disaster occurrence in libraries are rare. If this claim is anything to by, it can then be concluded that librarians in Nigeria are yet to learn any lesson from the two fire disasters gutted the University of Jos two campus libraries' whole collection in 2013 and 2016 respectively [14].…”
Section: Discussion Of Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…On another hand, the result of this study corroborated that of Echezona, Ugwu and Ozioko [16] who noted that it has been an age long thinking of librarians that the chances of disaster occurrence in libraries are rare. If this claim is anything to by, it can then be concluded that librarians in Nigeria are yet to learn any lesson from the two fire disasters gutted the University of Jos two campus libraries' whole collection in 2013 and 2016 respectively [14].…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…This could affect Nigerians' general perception on disaster-whether natural or man-made. This may not be unconnected to why it has been reported that some librarians pay little or no attention to disaster preparedness, due to the assumption that Nigeria and indeed Africa are not prone to disasters and that library disasters are not widespread in the region [16]. Disaster preparedness embraces activities, programmes, policies as well as measures which are taken up before (to prevent or mitigate), during (to respond) and after (to recover) from the loss accompanying emergency.…”
Section: Librarians' Perception Of Disaster Preparedness In Nigerian mentioning
confidence: 99%
See 1 more Smart Citation
“…An online search of the scholarly literature on (1) academic libraries and disaster management and (2) the role of academic libraries and librarians in natural disasters and in providing health information, yields large positive results (for example, Newman, 2018;Clare, 2016;Newman and Harris, 2015;Iske and Lengfellner, 2015;Khalid and Dol, 2015;Abareh, 2014;Echezona, 2012;Corrigan, 2008;Kostagiolas et al, 2011;Ahenkorah-Marfo and Borteye, 2010;Trishanjit, 2009;Clareson and Long, 2006, amongst others); these, however, are about fires, floods, earthquakes and hurricanes, inter alia, and do not cover pandemics. This indicates that the literature on academic library pandemic management needs development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the case studies of disasters affecting university libraries, there has been few research studies conducted globally with specific focus on university librarian knowledge for library disaster management. Echezona, Ugwu & Ozioko (2012)…”
Section: Literature Reviewmentioning
confidence: 99%